Pengaruh Edukasi Kesehatan Terhadap Pengetahuan Kepatuhan Minum Obat Pasien Diabetes Melitus Tipe 2 Di Rumah Sakit Tk Ii Robert Wolter Mongisidi Manado - Nurfitrianingsi Muhammad; Engeline Kosegeran; Rahmat Hidayat Djalil (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Non-compliance with taking medication in diabetes mellitus sufferers will cause blood sugar levels to decrease or increase beyond normal limits and as a result will cause complications or death. There is a need for health education regarding knowledge of diabetes patient medication adherence to prevent this. This research was conducted using a quasi-experimental research method (one-group pre-post test design). The sample in this study was 29 respondents taken using purposive sampling instruments using SAP, lealeats and questionnaires. the collected data was processed using the SPSS 24 version of the computer program to be analyzed using the Mc.Nemar nonparametic test with a significance level (α) of 0.05. The results of the bivariate analysis show that there is an influence of health education on knowledge of the level of dringking compliance in patients with type diabetes mellitus. The value obtained is p = 0,000 which means that Ha is accepted and Ho is rejected. The conclusions in the research show that there is an influence of knowledge education on treatment compliance.